Mentally retarded children’s training to plan their own work during handicrafts lessons - Karvelis, V. (Psichologija, 1962)
The Soviet auxiliary school, when preparing their wards for independent life and societal work, organizes all the work so as to eliminate the retarded child’s mental and physical handicap. Work training performs a great role solving the auxiliary school students’ comprehensive development task and correcting their existing shortcomings. Auxiliary school experience shows that particularly good measures to raise the effectiveness of training by adjusting the mentally retarded child’s intellectual development is pedagogically correctly organized work-linked training at all educational stages, including the lower grades. Handicrafts play a major adjusting role in the auxiliary school lower grades (1-3). These activities generate favorable conditions not so much for physically- but rather for mentally-abnormal children to express themselves and develop. Therefore, it is important to organize the lessons of this subject in a way that mentally retarded children’s thinking is activated and developed, while at the same time corrected (do not be satisfied with merely mechanical work performance, as sometimes happens in practice). Analysis of observed handicrafts lessons and experimental activities shows that circumstances which are crucial for the correct development of mentally-abnormal children arise when they’re doing their practical work. The necessity to plan work is one of the circumstances of workflow. Individual operations are performed gradually in the production of each item. This is the result of a complex thinking process, i.e. when producing an object a child has to first know how to divide it into different parts in his imagination, review their interconnection methods, and provide the consistency with which to do the job. This stage of the workflow process is particularly difficult for a mentally retarded child. Therefore, it is important to teach a retarded child to plan work. The main condition for teaching children to plan their work is students’ ability to consistently perform separate workflow operations. This article and is aimed at in depth analysis of this issue.